Silicon and glass very large scale microfluidic droplet integration for terascale generation of polymer microparticles - Sagar Yadavali (Nature Portfolio, 2018)
Microfluidic-generated polymer microparticles have been shown to have superior pharmacological performance; yet, mass production remains a challenge to industrial application. Here, the authors present and test a device that incorporates arrays of microparticle generators for mass production.